Enhancing identification of nonaffective psychosis in register-based studies - Holm, Minna (Springer Nature, 2025)
The Finnish Quality of Psychosis Care Register assesses nonaffective psychosis (NAP) care, acknowledging treatment outside specialized psychiatric services. This approach, while providing a holistic view, raises concerns about diagnostic inaccuracies. Here, we studied situations where the register-based diagnosis might be inaccurate, and whether the first episode can be reliably identified using a 14-year wash-out period. People with first register-based NAP (ICD-10 F20-F29) between years 2010 and 2018 and without NAP diagnoses in 1996–2009 were identified from the Care Register for Health Care. A diagnosis of NAP was deemed unreliable before age 7, when dementia preceded NAP diagnosis, and when a NAP diagnosis had been assigned at admission or during psychiatric hospitalization but was not confirmed by discharge diagnosis. Despite a 14-year follow-back the first register diagnosis may miss the first treatment episode in older patients. Register-based studies on psychotic disorders should pay attention to exclusion criteria and to the definition of treatment onset. © The Author(s) 2024.